Prácticas sobre uso de pasta dental fluorada en preescolares, padres y profesores - Mattos-Vela, Manuel Antonio (2012)
Abstract Objective. Identify practices on the use of fluoridated toothpaste and its relationship with going to the dentist in preschool children, parents and teachers from public educational institutions in the district of La Molina, Lima, Peru. Methods. Cross sectional study. Two questionnaires were used, one aimed at parents (who explored habits from child and parent), and other one aimed to teachers. Results. Almost all children brushed their teeth and used toothpaste. The children start using toothpaste at 2 years old (40.5%) and a moderate amount (60.8%), do not swallow toothpaste when brushing (62.9%) and with monitoring during brushing (77, 6%). Almost all parents and teachers brush their teeth, and used toothpaste. The applying of toothpaste in preschool children was significantly associated (p = 0.028) with visit to the dentist. Conclusions. The practice in the use of fluoride toothpaste in preschool children need to be improved with proper oral health education to this population.